Strategi Komunikasi Politik Pasangan Christian Widodo – Serena Francis dalam Pemilihan Walikota Kupang pada Pilkada 2024 - Rex Tiran; Philips Y.N.Ndoda; Stephanus Marselino Tukan (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
This study explains the POLITICAL COMMUNICATION STRATEGY OF THE CHRISTIAN WIDODO – SERENA FRANCIS PAIR IN THE MAYORAL ELECTION OF KUPANG IN THE 2024 REGIONAL ELECTION. This study aims to determine the political strategy of the Christian Widodo – Serena Francis pair to win the 2024 regional election in Maulafa sub-district. The approach in this study is Qualitative. The results of the study show that the candidate pair for Mayor and Deputy Mayor of Kupang, dr. Christian Widodo and Serena Francis (CS'an), led the vote count in the 2024-2029 Kupang City Regional Head Election (Pilkada). Based on the provisional results of the C1 Plano tabulation recapitulation conducted by the CS-an Center, which was collected from 552 Polling Stations (TPS), this pair won 36.29% of the vote or 68,853 votes, significantly ahead of their closest competitor, Jefri-Adinda, who won 26.4% of the vote or 50,192 votes. CS'an dominated in five of the six sub-districts in Kupang City, namely Kota Lama, Kelapa Lima, Maulafa, and Oebobo. It can be concluded that Christian Widodo and Serena Francis' political strategies show consistency in building narratives that are relevant to the needs of the community, especially in the areas of local economic empowerment and public service reform. They optimize social media and digital communication to reach young voters, strengthen public engagement, and shape their image as adaptive and modern leaders. Both build strategic coalitions with civil society groups and youth organizations that expand their electoral reach, especially in urban and semi-urban areas. Serena Francis specifically raises the issue of women's representation and political inclusivity, which has succeeded in attracting the attention of women and marginalized groups.